Reading, writing, and errant subjects in inquisitorial Spain - Prendergast, Ryan C. (Ashgate, 2011)
Introduction: specters of control -- Texts produced, consumed, and controlled -- Frontiers of Muslim and Morisco identity -- Inscriptions of transgression, confession, and punishment -- Specters, stages, and spectacles